The impact of internet adaptability on internet addiction: the serial mediation effect of meaning in life and anxiety - Wang, Weijun; Ma, Shihao; Han, Xinheng; Zhao, Xin (Frontiers in Psychiatry, 2023)
Introduction: Previous research has demonstrated the significant role of individual characteristics in adolescent Internet addiction. In line with this, our previous research has introduced the concept of "Internet adaptability" as a potential factor that enables individuals to effectively cope with the negative consequences of Internet use.However, further investigation is required to understand the impact of Internet adaptability on problematic Internet use, including Internet addiction, as well as its associated internal psychological factors. To address this research gap, the present study aims to examine the impact of Internet adaptability on internet addiction and explore the mediating roles of meaning in life and anxiety within this relationship.Methods: A questionnaire was used to survey 2144 adolescents from high schools in central China to investigate internet adaptability, meaning in life, anxiety, and internet addiction.The results revealed a significant negative correlation between Internet adaptability and adolescent internet addiction (r = -0.199, P < 0.01). Furthermore, our results indicated that Internet adaptability negatively predicts internet addiction (β = -0.086, P < 0.001). Additionally, mediation analyses revealed that both meaning in life (β = -0.060, P < 0.001) and anxiety (β = -0.032, P < 0.01) mediate the relationship between Internet adaptability and internet addiction. Moreover, a serial mediation effect involving meaning in life and anxiety was observed between Internet adaptability and internet addiction (β = -0.027, P < 0.001).These findings suggest that Internet adaptability plays an important role in alleviating individual internet addiction. Our results indicate that increasing individuals' sense of meaning in life can help reduce anxiety, thereby potentially reducing internet addiction.